2017
DOI: 10.1038/s41598-017-02940-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambient anthropogenic noise but not light is associated with the ecophysiology of free-living songbird nestlings

Abstract: Urbanization is associated with dramatic increases in noise and light pollution, which affect animal behaviour, physiology and fitness. However, few studies have examined these stressors simultaneously. Moreover, effects of urbanization during early-life may be detrimental but are largely unknown. In developing great tits (Parus major), a frequently-used model species, we determined important indicators of immunity and physiological condition: plasma haptoglobin (Hp) and nitric oxide (NOx) concentration. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…Chronic noise is known to elevate haptoglobin immune response, which can be energetically costly (Raap et al. ), although a recent study found no correlation between decreased body size and nutritional stress (Meillère et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic noise is known to elevate haptoglobin immune response, which can be energetically costly (Raap et al. ), although a recent study found no correlation between decreased body size and nutritional stress (Meillère et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Raap et al. ). Animals may also have to change their territorial behaviors in noisy urban conditions, such as approaching more closely to be able to hear an acoustic signal, which could lead to aggressive territorial interactions and potentially affect body condition, reproduction, and survival (Phillips and Derryberry ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have been conducted under controlled laboratory conditions with restricted application to free‐ranging mammals. To our knowledge, only four studies have examined the effect of artificial light on oxidative status using experimental field studies on the great tit ( Parus major) (Casasole et al., ; Raap et al., ; Raap, Casasole, Pinxten, & Eens, ; Raap, Pinxten, Casasole, Dehnhard, & Eens, ) and no study has examined the impacts on a mammal under similar field conditions (Isaksson, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, also indications that suggest that nest boxes may shield animals from direct effects of ALAN. Experimental ALAN inside a nest box affected nestling physiology (Raap, Casasole, Pinxten, & Eens, ), but ambient light pollution at the nest box was unrelated to nestling physiology (Raap, Pinxten, Casasole, Dehnhard, & Eens, ). Whether ambient light pollution leads to altered sleep behavior of birds inside nest boxes (cavities), similar to what has been found in experiments with ALAN inside a nest box using free‐living blue and great tits (Raap et al., , , ; Sun et al., ), needs to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during winter, our previous experiments with ALAN inside nest boxes also showed most effects to occur during the morning (Raap et al., ; ). We used a light intensity for our experimental treatment that was similar to intensities measured at nest boxes located near street lights (≤16 m; average 1.6 ± SE 0.6 lux, N = 16; Casasole et al., ; Raap et al., ), with street lights themselves often having intensities of around 10–40 lux (Gaston, Davies, Nedelec, & Holt, ). The intensity that we used may therefore be experienced by animals near street lights.…”
Section: Introductionmentioning
confidence: 99%